Mewartakan Keselamatan Kristus dalam Budaya Ruwatan: “Model Dialog Interreligius” Ajaran Katolik dengan Kejawen - Caesario, Yusuf Dimas (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2019)
Ever since the Second Vatican Council, interreligious dialogue has become a prominent theme in theological discussion and practice. The main issue is how the Christian message could be made known and comprehended properly by people of other faiths or other religious traditions. The writer tries to explore the possibility of dialoguing with the so-called Kejawen communities (the religion of Java), particularly on the issue of Ruwatan, a cleasing rite for ‘unfortunate people’ and forgiveness to sinners. He proposes then the prophetic model of interreligious dialogue that could be applied particularly to the religious theme of Baptism and Ruwatan.